1975
DOI: 10.1007/bf00312541
|View full text |Cite
|
Sign up to set email alerts
|

Movement-associated cortical potentials in unilateral cerebral lesions

Abstract: Movement-associated cortical potentials (MP) associated with thumb-opposition or fist-clenching were studied in 20 patients with unilateral cerebral lesions and in 8 healthy subjects. MP was abnormal in 16 patients. The most frequent abnormality was an attenuation of the N component or readiness potential, recorded on the central region contralateral to the contracting muscle, on the affected hemisphere. The occurrence and severity of MP abnormalities seem to be influenced by an intensity and extension of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…MRPs constitute a waveform that is obtained by taking the ÔaverageÕ EEG, in terms of onset of movement or myo-electrical activity of the prime mover [3,4]. Many studies demonstrated topographical alterations of some MRP components during the recovery period after a stroke [5][6][7][8][9][10][11]. The analysis of MRP, however, presents methodological difficulties because of its low signal to noise ratio [12].…”
Section: Introductionmentioning
confidence: 99%
“…MRPs constitute a waveform that is obtained by taking the ÔaverageÕ EEG, in terms of onset of movement or myo-electrical activity of the prime mover [3,4]. Many studies demonstrated topographical alterations of some MRP components during the recovery period after a stroke [5][6][7][8][9][10][11]. The analysis of MRP, however, presents methodological difficulties because of its low signal to noise ratio [12].…”
Section: Introductionmentioning
confidence: 99%
“…11 However, only few studies exist that examined hemiparetic patients. [12][13][14] Moreover, sample sizes were small, or patients with brain lesions of different etiologies were examined.…”
mentioning
confidence: 99%
“…Abschlicßond sei noch erwähnt, daß unsere Ergebnisse nicht im Widerspruch zu den bereits bekannten Veröffentlichungen (7, 16,18). stchen.…”
Section: Movement -Helated Potentials -Readiness Potenlials -Vobntaryunclassified